(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Criminal liability is a foundational concept in criminal law, representing the conditions under which individuals are held legally responsible for criminal acts. This article explores the theoretical framework, legal definitions, and essential elements of criminal liability, such as mens rea (criminal intent) and actus reus (criminal act). It also examines how criminal liability is established and interpreted across national and international legal systems. Judicial cases and examples are provided to illustrate the practical application of this concept. The paper concludes by evaluating the role of criminal liability in ensuring justice and maintaining public order.